CT-assessed large airway involvement and lung function decline in eosinophilic asthma: The association between induced sputum eosinophil differential counts and airway remodeling. (20th October 2016) - Inoue, Hideki; Ito, Isao; Niimi, Akio; Matsumoto, Hisako; Matsuoka, Hirofumi; Jinnai, Makiko; Takeda, Tomoshi; Oguma, Tsuyoshi; Otsuka, Kojiro; Nakaji, Hitoshi; Tajiri, Tomoko; Iwata, Toshiyuki; et al.
Abstract: Objectives : Eosinophilic asthma (EA) is a distinct clinical phenotype characterized by eosinophilic airway inflammation and airway remodeling. Few studies have used computed tomography (CT) scanning to assess the association between sputum eosinophil differential counts and airway involvement. We aimed to investigate the clinical characteristics and airway involvement of EA, and to examine the correlation between induced sputum eosinophil differential counts and CT-assessed airway remodeling. Methods : We retrospectively divided 63 patients with stable asthma receiving inhaled corticosteroids into 2 groups: 26 patients with EA (sputum eosinophil >3%) and 37 patients with non-eosinophilic asthma (NEA). Clinical measurements such as spirometry, fractional exhaled nitric oxide levels (FeNO), and CT-assessed indices of airway involvement were compared between the groups. Multivariate analysis was performed to identify determinants of the percentage of wall area (WA%). Results : The EA group had significantly longer asthma duration, lower pulmonary function, and higher FeNO than the NEA group. Also, the EA group had higher WA% and smaller airway luminal area than the NEA group. Sputum eosinophil differential counts and WA% were positively correlated. The multivariate linear regression analysis showed that the factors associated with WA% included sputum eosinophil differential counts, age, and body mass index. However, asthma duration was not associated with WA%. Our CT-assessed findings demonstrated large airway involvement in EA, and we observed a positive association between induced sputum eosinophil differential counts and WA%. Conclusions : The findings indicate that induced sputum eosinophil differential counts may be associated with airway remodeling in patients with stable asthma.